Reframing Complexity: A Four-Dimensional Approach to Organizational Di agnosis, Development and Change - Gallos, Joan V. (Organization Development: A Jossey-Bass Reader, 2006)
This is the third book in the Jossey–Bass Reader series, Organization Development: A Jossey–Bass Reader. This collection will introduce the key thinkers and contributors in organization development including Ed Lawler, Peter Senge, Chris Argyris, Richard Hackman, Jay Galbraith, C ooperrider, Rosabeth Moss Kanter, Bolman & Deal, Kouzes & Posner, and Ed Schein, among others. "Without reservations I recommend this volume to those students of organizational behavior who want an encyclopedia of OD to gain a perspective on the past, present, and future...." Jon athan D. Springer of the American Psychological Association.